The Effectiveness of An Internet of Things (IoT)-based Virtual Science Laboratory on Nervous System Material in Science Course - Setyo Eko Atmojo; Ari Kusuma Wardana; Taufik Muhtarom (Jurnal Paedagogy, 2024)
This study aims to test the effectiveness of the Internet of Things (IoT)-based virtual science laboratory on nervous system material in science lectures. The research method used was an experiment with a pretest-posttest control group design, with the research subjects being randomly selected A3 and A4 class students in the PGRI Yogyakarta University PGSD study program who take science courses. Data was collected by giving a pre-test and post-test and measuring n-gain to determine the increase in concept understanding after using a virtual science laboratory. Data analysis was carried out using the t-test to test the significant difference between the pre-test and post-test results and the n-gain test to measure the effectiveness of virtual science laboratories in improving students' concept understanding. The results of this study indicated that the Internet of Things (IoT)-based virtual science laboratory on nervous system material effectively improves students' understanding of concepts. It can be seen from the average n-gain result of 0.72 in the experimental group, which shows a high increase in concept understanding. The t-test results showed a significant difference between the control group and the experimental group in terms of the effectiveness of the IoT-based virtual science laboratory on nervous system material.